Preaching the Gospel of Luke : proclaiming God's royal rule - Nickle, Keith Fullerton, 1933- (Westminster John Knox Press, 2000)
"Blending the latest in Lukan scholarship with the practical needs of the weekly preacher, New Testament scholar Keith Nickle provides clear, interesting, and instructive comments on the third Gospel. But Preaching the Gospel of Luke offers more than mere exposition. After each passage, three to five possibilities are proposed for how to preach every text - creative and pertinent suggestions that can help preachers apply the words of the biblical narrative to the lives of today's churchgoers. Proclaiming the royal rule of God is the theme of Luke, and this commentary helps that message come alive in the preaching moment."--Jacket.